Interactions between Individuals on the Autism Spectrum and the Police: The Fears of Parents, Caregivers, and Professionals. (28th November 2020) - Wallace, Danielle; Herbert, Jessica; Tyler, David; McGee-Hassrick, Elizabeth
Abstract: Using data from a survey of parents, guardians, caregivers, and professionals, we couple qualitative coding with descriptive statistics to show how common it is for respondents to fear future police contact for the individual with autism spectrum disorder (ASD) in the respondents' lives and what inspires that fear. Nearly, 60% of respondents were reported being fearful of future police contact. Respondents characterized their fear in the following ways: the potential for police officers to misunderstand behaviours common amongst individuals with ASD generally and see those behaviours as non-compliance, ineffective, or difficult communication with minimally individuals with ASD and the emergence of aggressive behaviours from individuals with ASD during police contact. Respondents also expressed concern about the potential for police misuse of force. We conclude by discussing the ramifications of fear of police contact for police training as well as parents, caregivers, and individuals with ASD.